Problems of Teachers in Providing Assessments of Students' Attitudes in the Learning Process - Sukmawari Pasino; Elihami Elihami (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aims to find out how teachers assess student attitudes, teacher difficulties in assessing student attitudes, and the efforts made by teachers in overcoming difficulties in assigning values ​​to students' attitudes in the learning process based on the 2013 curriculum in elementary school. Research subjects as six teachers were selected using the purposive sampling technique. The approach used in this research is a qualitative approach with a descriptive type of research. Data collection techniques use observation and interviews. The data were analyzed using inductive logic, namely from specific to general. The conclusions of this study indicate that the teacher provides an assessment of student attitudes in the learning process based on the 2013 curriculum in elementary school by observing or making direct observations of students' attitudes during the learning process. The difficulty of teachers in assessing student attitudes in the learning process based on the 2013 curriculum in elementary schools in the limited time, the large number of students in one class, and the difficulty in directing students to instill good attitudes following learning objectives. Efforts made by teachers in overcoming difficulties in assigning grades to students' attitudes in the learning process based on the 2013 curriculum in elementary schools are by discussing with parents of students, coordinating with other teachers, and asking other students to get detailed information.